SOME METHODOLOGICAL ASPECTS OF WORKING WITH TEXT IN FOREIGN LANGUAGE LESSONS (Academia Science Repository, 2023)
The article describes the methodological aspects of working with text in a foreign language class as well as exemplary exercises f or each stage of working with text.